2005
DOI: 10.1038/sj.bjc.6602511
|View full text |Cite
|
Sign up to set email alerts
|

Cancer following hip and knee arthroplasty: record linkage study

Abstract: Concerns have been raised that degradation of implants used in hip and knee arthroplasty may lead to an increased risk of some cancers, particularly those of the haematopoietic, lymphatic and urinary systems. We used linked statistical records of hospital admissions and deaths to compare cancer rates in cohorts of people who had undergone hip or knee arthroplasty with a comparison cohort. We did not find an elevated risk for cancer, overall, in either the hip or knee cohort or in both combined (rate ratio for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
23
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 13 publications
(16 reference statements)
4
23
0
Order By: Relevance
“…These metallic ions may have a direct mutagenic effect on the local environment, predisposing to lymphomagenesis [18]. Furthermore, metallic ions released into the circulation may have a similar effect at a systemic level, a theory supported by recent data from epidemiological studies suggesting an increased incidence of systemic NHL after total knee replacement [19,20,21,22]. …”
Section: Discussionsupporting
confidence: 50%
“…These metallic ions may have a direct mutagenic effect on the local environment, predisposing to lymphomagenesis [18]. Furthermore, metallic ions released into the circulation may have a similar effect at a systemic level, a theory supported by recent data from epidemiological studies suggesting an increased incidence of systemic NHL after total knee replacement [19,20,21,22]. …”
Section: Discussionsupporting
confidence: 50%
“…In studies of cohorts of people with non-malignant disease, followed for subsequent cancer risk, and compared with the reference cohort, the reference cohort is known to give cancer rates that are highly plausible. Using the reference cohort as a comparator, we have reported on combinations of non-malignant disease and subsequent cancer that show no elevation or diminution of risks when none are expected [18][19][20]; high cancer rates when these are expected (e.g. high rates of colon cancer in people with inflammatory bowel disease [21], high rates of liver and pancreatic cancer in people with chronic non-malignant liver disease or pancreatitis [22]); and low rates when expected (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…A comparison cohort was constructed by identifying the first admission for each individual with various medical and surgical conditions (listed in table footnotes) but excluding those with a record of diabetes. This is based on a 'reference' group of conditions that has been used in other studies of associations between non-malignant diseases and cancer [17][18][19][20][21][22]. We followed the standard epidemiological practice, when hospital controls are used, of selecting a diverse range of conditions, rather than relying on a narrow range (in case the latter are themselves atypical in their risk of subsequent disease).…”
Section: Methodsmentioning
confidence: 99%
“…Two early cohort studies of cancer risk following THA found an increased risk of lymphohaematopoietic malignancies (Gillespie et al , 1988; Visuri and Koskenvuo, 1991), but apart from an excess of multiple myeloma emerging during long-term follow-up (Signorello et al , 2001), other studies (Mathiesen et al , 1995; Nyrén et al , 1995; Gillespie et al , 1996; Visuri et al , 1996, 2010; Olsen et al , 1999; Paavolainen et al , 1999; Goldacre et al , 2005; Mäkelä et al , 2012) have not shown an excess risk of these cancers. However, some other studies have reported excess risks of melanoma of the skin (Nyrén et al , 1995; Olsen et al , 1999; Signorello et al , 2001; Mäkelä et al , 2012), prostate cancer (Nyrén et al , 1995; Signorello et al , 2001), kidney cancer (Nyrén et al , 1995), and basal cell carcinoma of the skin, specifically in patients with modern generation metal-on-metal hip replacements (Mäkelä et al , 2012).…”
mentioning
confidence: 99%